For a history of translation in Spanish America - Bastin, Georges (Íkala, Revista de Lenguaje y Cultura, 2003)
In this article a general panorama of the history of translation in Hispanic America is presented, from the time of the Conquest to the present day. With this aim in mind, four historical periods have been identified, within which insight into the people, documents and events that illustrate the state of translating in each era, is given. This article, that only attempts to sketch a history still to write, is an invitation to study the translating patrimony of the region, which is, undoubtedly, much richer than has been previously reported. Received: 23-04-03 / Accepted: 10-06-03. How to reference this article: Bastin, G. (2003). Por una historia de la traducción en Hispanoamérica. Íkala. 8(1), pp. 193 – 217